Geochemical modelling of the speciation, transport, dispersal and fate of metal contaminants in water systems in the vicinity of tailings storage facilities - Grover, Bronwyn Patricia Camden (My University, 2016)
Gold mining of the Witwatersrand Basin reefs has been responsible for the rise of Johannesburg as an economic centre of South Africa. While mining provided a base for business and infrastructure development for the region, it has also generated social and environmental problems for the country. Tailings storage facilities (TSFs), a common sighting around Johannesburg and across the entire basin, have been built to contain the processed waste following extraction of gold from the pyrite containing quartzite ore. When the fine grained waste is exposed to atmospheric conditions, oxidation of remnant sulphides occurs resulting in acidic, metal rich and sulphate rich plumes that enter the environment through surface and groundwater systems. This thesis sought to better understand the release, transport, dispersal and fate of metals emanating from TSFs and their remnant footprints on the Witwatersrand. These metals included aluminium, copper, chromium, iron, manganese, nickel and uranium and are known to be toxic to humans depending on their concentration and speciation. Traditionally, analytical methods have been employed in studies focussing on the characterisation of some of these processes in the region. While these studies have generally conducted quantitative assessment of the extent of pollution, little comprehensive interrogation and fingerprinting of the processes that are influential in determining the potential risk posed by metals has been done. This has largely been due to the shortcomings of analytical methods to determine these. To this end, this research has employed geochemical modelling to complement the traditional analytical methods. The approach to study the release of metals from TSFs involved assessment of the partitioning of metals within tailings and their potential release using batch and sequential extraction methods. Processes of metal release within the tailings were simulated through geochemical modelling (using the PHREEQC and Geochemist’s Workbench codes). The simulations were based on the percolation of rainwater through these layers and the changes in its chemistry along the path. The potential seepage of this plume along the path was then correlated to observed efflorescent mineral crusts that are temporary sinks for metals and are a common feature in the vicinity of the tailings and water bodies such as ponds and streams. The potential impact of the mineral crusts on the water chemistry of receiving water systems following their dissolution was assessed using forward geochemical modelling. The transport of the metals in groundwater was also studied. This involved simulations of the transition in chemistry of a plume from a TSF along an aquifer of known composition. This was based on a 1-D reactive transport model constructed using information from sequential extraction work on the aquifer rock (to identify the key minerals to consider) and site data (mainly flow rates) from previous studies. The processes occurring in the removal of metals from acid mine drainage (AMD) through a permanent sink in the form of a pump-and-treat plant in the Central Goldfield of the basin were simulated using PHREEQC. The findings from the research showed that two different plumes were produced from an abandoned TSF as a result of rainwater percolation, notably a plume produced from the dissolution of secondary salts formed in the oxidised layer and a sulphuric acid rich plume in the unoxidised layer. These differences were apparent in the geochemical composition of the mineral crusts collected on the walls of tailings dumps and from a pond into which the plumes were draining. On dissolution, mineral crusts were found to produce acidic solutions with crusts containing predominantly Fe producing pH values below 3. The simulated dissolution of various types of mineral crusts gave insight into the impact of minerals present in the smallest amount. This showed that the bulk mineralogy as determined by analytical techniques such as PXRD and remote sensing could not be used with confidence to deduce the impact of the mineral crusts on receiving water bodies. The characteristics of surface plumes released from tailings TSF were compared to other water systems in the area around Soweto, with complementary interpretation conducted using chemometric methods. From principal component analysis (PCA), surface water systems were found to form distinct groups largely influenced by mineral solubility, alkalinity and dissolved oxygen content. The 1-D reactive transport simulations involved acidic, metal and sulphate rich water ingressing the aquifer (below the TSF). Several scenarios were modelled including simulations with different dolomite contents; allowing for surface complexation and the presence of cation exchange surfaces. At a point 500 m from the water ingress in the dolomite rich aquifer, Fe and Mn were largely precipitated out (as confirmed by sequential extraction results on the aquifer rock) while the sulphate concentration was reduced by almost half. On the other hand, Ca concentrations were conservative largely because of continuous dissolution of dolomite and precipitation of gypsum along the flow path. The simulations of the high density sludge treatment plant involved forward modelling of the treatment process with the sludge responsible for the removal of trace metals from the incoming acid mine drainage. The model can be of use for cost and process optimisation at the facility. This research has had notable outputs in the form of publications; models on metal release, transport and attenuation; and models on pump-and-treat processes. These will form an important repository of information and for benchmarking any further studies related to AMD.
A thesis submitted to the Faculty of Science, University of the Witwatersrand, Johannesburg, in fulfilment of the requirements for the degree of Doctor of Philosophy. Johannesburg, 2016.
Keywords: Geochemical modeling; Water systems--Effect of contaminated metals on; Tailings embankments--Drainage system--Mathematical model; Tailings dam